Curcumin-loaded PLGA-PEG nanoparticles conjugated with B6 peptide for potential use in Alzheimer's disease - Shengnuo Fan; Yuqiu Zheng; Xuan Liu; Wenli Fang; Xiaoyu Chen; Wang Liao; Xiuna Jing; Ming Lei; Enxiang Tao; Qiulan Ma; Xingmei Zhang; Rui Guo; et al. (Taylor & Francis Group, 2018)
Alzheimer's disease is a neurodegenerative disorder mainly characterized by β-amyloid deposit and tau hyperphosphorylation with no curative treatments. Curcumin (Cur) has been proved to have potential use in Alzheimer's disease with its anti-amyloid, anti-inflammatory, and anti-oxidant properties, etc. However, its hydrophobicity and low bioavailability hinder its application. In this paper, we designed a novel brain-target nanoparticle, poly(lactide-co-glycolide)-block-poly(ethylene glycol) (PLGA-PEG) conjugated with B6 peptide and was loaded with Cur (PLGA-PEG-B6/Cur) and administered it into HT22 cells and APP/PS1 Al transgenic mice. The in vitro assays including dynamic light scattering (DLS), flow cytometry (FCM), red blood cell (RBC) lysis, and thromboelastography (TEG) analysis indicated that this nanoparticle could narrow the diameter of Cur, increase its cellular uptake and possess good blood compatibility. The results from Morris water maze proved that PLGA-PEG-B6/Cur could tremendously improve the spatial learning and memory capability of APP/PS1 mice, compared with native Cur. The ex vivo assays including Bielschowsky silver staining, immunostaining, and western blotting demonstrated that PLGA-PEG-B6/Cur could reduce hippocampal β-amyloid formation and deposit and tau hyperphosphorylation. Thus, we suggested that PLGA-PEG-B6/Cur nanoparticles would be of potential and promising use for the treatment of Alzheimer's disease.